The Holocaust by bullets : a priest's journey to uncover the truth behind the murder of 1.5 million Jews - Desbois, Patrick (New York : Palgrave Macmillan, 2008)
In this heart-wrenching book, Father Patrick Desbois documents the daunting task of identifying and examining all the sites where Jews were exterminated by Nazi mobile units in the Ukraine in WWII. Using innovative methodology, interviews, and ballistic evidence, he has determined the location of many mass gravesites with the goal of providing proper burials for the victims of the forgotten Ukrainian Holocaust. Compiling new archival material and many eye-witness accounts, Desbois has put together the first definitive account of one of history's bloodiest chapters.--From publisher description.
Includes bibliographical references (p. 221-228) and index.
Keywords: Desbois, Patrick; Jews -- Persecutions -- Ukraine; Holocaust, Jewish (1939-1945) -- Ukraine -- Personal narratives; Ukraine -- Ethnic relations